Reflections on prejudice and intergroup relations. (October 2016) - Molina, Ludwin E; Tropp, Linda R; Goode, Chris
Highlights: This review focuses on intergroup contact, its psychological processes, and outcomes of contact. Intergroup relations can be defined by ingroup love, outgroup hate, direct and indirect prejudice. Meta-analytic research shows that intergroup contact is associated with reduced prejudice. Social identity theory stresses how group identities inform intergroup relations. Intergroup relations research examines outcomes like prejudice reduction and collective action. Abstract : Intergroup relations examine how people of different backgrounds and groups interact with one another. Intergroup encounters can range from highly positive (e.g., friendships) to extremely negative (e.g., genocides) so the charge of intergroup relations is to illuminate the social psychological processes that influence such encounters. The present review highlights four themes: (1) intergroup prejudice as ingroup love versus outgroup hate; (2) contemporary forms of intergroup prejudice; (3) how contact between groups may reduce intergroup prejudice; and (4) how material concerns (e.g., distribution of resources) and psychological processes (e.g., group identification) further influence intergroup relations. The review concludes with thoughts on the state of intergroup relations research and its relevance to contemporary society.